Phylogenetic and morphological evidence reveals the association between diet and the evolution of the venom delivery system in Neotropical goo-eating snakes. Issue 1 (31st December 2023) - Oliveira, Leonardo De; Grazziotin, Felipe Gobbi; Sánchez-Martínez, Paola Maria; Sasa, Mahmood; Flores-Villela, Oscar; Prudente, Ana Lúcia Da Costa; Zaher, Hussam
Abstract : Advanced endoglyptodont snakes share a complex but homologous venom delivery system associated with the upper jaw and its dentition. Recently, a remarkable novel lower jaw venom delivery system was described for the Neotropical dipsadine radiation of goo-eating snakes. While most dipsadines are opistoglyphous and exhibit large, mainly serous venom glands associated with the upper jaw and supralabial glands, goo-eating dipsadine snakes are aglyphous and lack serous upper labial venom glands. Here, we provide new morphological and histological information on the oral glands and maxillary dentition of representatives of the major lineages of dipsadines that help trace the evolutionary steps that shaped the venom delivery system of dipsadines. We performed a maximum likelihood analysis on a molecular dataset that includes 443 terminals and seven loci. Our results show that goo-eating dipsadines form a monophyletic assemblage that includes the genus Adelphicos for the first time, along with Geophis, Atractus, Ninia, Chersodromus, Tropidodipsas, Sibon, and Dipsas . We also provide the first evidence of a complete shift from an upper jaw to a lower jaw venom delivery system associated with their specialized feeding behaviour. Unlike other dipsadines who exhibit typical endoglyptodont anteroposteriorly ridged posterior maxillary teeth, goo-eating dipsadines have uniform lateromedially ridged teeth throughout their maxilla. Our results indicate that the loss of the endoglyptodont venom delivery system occurred in the most recent common ancestor of goo-eating dipsadines, probably resulting from the loss of the embryonic posterior maxillary lamina responsible for the development of the venom delivery system.